Examining mobile game’s loyalty strategy: The case of honkai star rail - Pamungkas, Angga Suda; Ramadania, Ramadania; Heriyadi, Heriyadi; Pebrianti, Wenny (Junal Ilmu Manajemen, 2025)
The mobile gaming industry is experiencing exponential growth, as evidenced by its contribution of half the revenue to the global gaming market. Honkai Star Rail, a product of Mihoyo, has secured the prestigious position of Best Mobile Game Award in 2023. A year post-launch, Honkai Star Rail has maintained its status as a top-tier mobile game, consistently ranking among the top 15 grossing applications. The effectiveness of strategies implemented by game developers can significantly enhance customer loyalty and repurchase behaviour. This phenomenon underscores the dynamic nature of the mobile gaming sector. It highlights the critical role of strategic planning in sustaining market position and fostering consumer engagement in this highly competitive digital ecosystem. Therefore, this research examines whether the variables of In-game Reward, Flow Experience, and Content Marketing mediated by Customer Satisfaction can affect the player’s loyalty. Researchers use quantitative methods and S.P.S.S. and Amos 26 applications to process and test the data in this research process. Based on the data collected from 225 respondents from Indonesia, in-game rewards, flow experience, and content marketing significantly affect the loyalty of Honkai Star Rail’s players, with the mediating variable of satisfaction.